Vehicular networking : automotive applications and beyond - Emmelmann, Marc; Bochow, Bernd; Kellum, C. Christopher (Intelligent transportation systems (Chichester, England), 2010)
During the last 15 years, the interest in vehicular communication has grown, especially in the automotive industry. Due to the envisioned mass market, projects focusing on Car-to-X communication experience high public visibility. This book presents vehicular communication in a broader perspective that includes more than just its application to the automotive industry. It provides, researchers, engineers, decision makers and graduate students in wireless communications with an introduction to vehicular communication focussing on car-to-x and train-based systems.: Emphasizes important perspectiv.